ANALISIS USAHATANI JAGUNG KUNING DAN KONTRIBUSINYA TERHADAP PENDAPATAN PETANI DI KECAMATAN BONTOLEMPANGAN KABUPATEN GOWA - Hardiyono Hardiyono (Lembaga Penelitian, Publikasi dan Pengabdian pada Masyarakat (LP3M) Nobel Indonesia, 2019)
Zea mays ssp. mays farming in Gowa Regency, especially Bontolempangan Subdistrict, is a commodity that has the potential to be developed and can increase farmers' income. This study was directed to find out how Zea mays ssp. mays farming and its contribution to the income of farmers in Bontolempangan District, Gowa Regency. The income of Zea mays ssp. mays farmers is Rp. 5,061,919.00 per hectare per planting season, with an R / C ratio of 3.69 and a B / C ratio of 2.69, and the margin received for each marketing channel varies. For channel I, the collecting trader gets a profit of Rp. 90 / kg, marketing margin Rp. 150 / kg. Big traders get a profit of Rp. 130 / kg, marketing margin of Rp. 200 / kg. Retailers get a profit of Rp. 230 / kg, marketing margin of Rp. 300 / kg. For channel II, large traders get a profit of Rp. 255 / kg, marketing margin Rp. 350 / kg. Retailers get a profit of Rp. 230 / kg, marketing margin of Rp. 300 / kg. Channel III retailers get a profit of Rp. 520 / kg, marketing margin Rp. 650 / kg